1995
DOI: 10.1246/bcsj.68.1030
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Fixed-Bed Operations over K2CO3-on-Carbon for the Recovery of Carbon Dioxide under Moist Conditions

Abstract: A modified chemical-absorption method capable of cyclic fixed-bed operations under moist conditions for the recovery of carbon dioxide from flue gases has been proposed employing K2CO3-on-carbon. Deliquescent potassium carbonate was favorably supported on activated carbon as well as on bound carbon dioxide in the presence of water vapor by the following reaction: After breakthrough, the entrapped carbon dioxide was released by the decomposition of hydrogencarbonate at a higher te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 1 publication
3
60
0
Order By: Relevance
“…Alkali metal carbonates such as Na 2 CO 3 and K 2 CO 3 react with CO 2 and H 2 O and transform to alkali metal hydrogen carbonates after CO 2 absorption by the following reaction, M 2 CO 3 þ CO 2 þ H 2 O 2MHCO 3 ðM ¼ Na; KÞ [18][19][20][21][22][23][24][25][26][27][28][29]. Water vapor is always necessary in forming potassium hydrogen carbonate in all reactions as shown in the absorption mechanism, unlike alkaline earth metalbased sorbents, while moisture contained in the flue gases as high as 8-17 vol.% negatively affected the adsorption capacity of molecular sieves [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alkali metal carbonates such as Na 2 CO 3 and K 2 CO 3 react with CO 2 and H 2 O and transform to alkali metal hydrogen carbonates after CO 2 absorption by the following reaction, M 2 CO 3 þ CO 2 þ H 2 O 2MHCO 3 ðM ¼ Na; KÞ [18][19][20][21][22][23][24][25][26][27][28][29]. Water vapor is always necessary in forming potassium hydrogen carbonate in all reactions as shown in the absorption mechanism, unlike alkaline earth metalbased sorbents, while moisture contained in the flue gases as high as 8-17 vol.% negatively affected the adsorption capacity of molecular sieves [9].…”
Section: Introductionmentioning
confidence: 99%
“…Alkali metal-based sorbents were employed in CO 2 absorption at low temperatures (50-70°C) with thermal regeneration easily occurring at low temperatures below 200°C. Hirano et al have proposed a modified chemical-absorption method capable of cyclic fixed-bed operations for the recovery of carbon dioxide from flue gases over K 2 CO 3 -on-carbon [19]. Deliquescent potassium carbonate was supported on activated carbon to adapt for cyclic fixed-bed operations and showed breakthrough curves with sharp frontal edges [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when CO 2 reacts with Na 2 CO 3 , the rate of global carbonation is rather slow (Zhao et al 2009). The CO 2 adsorption and regeneration using potassium-based sorbents with several supports such as activated carbon (Hirano et al 1995;Hayashi et al 1998;Shigemoto et al 2006), TiO 2 , SiO 2 , MgO, ZrO 2 , CaO and Al 2 O 3 were also reported in previous studies (Okunev et al 2000(Okunev et al , 2003Lee et al 2004;Liang et al 2004). Al 2 O 3 is one of the ideal materials used as a sorbent support.…”
Section: Introductionmentioning
confidence: 54%
“…Hirano et al 38 and Hayashi et al 39 reported that the formation of active species, K 2 CO 3 ·1.5H 2 O, plays an important role in the CO 2 capture capacity and that a vapor pretreatment process substantially improved CO 2 capture capacity. 40 The experimental results showed that the CO 2 capture capacity could be enhanced due to the conversion of the K 2 CO 3 phase to the K 2 CO 3 ·1.5H 2 O phase through the K 4 H 2 (CO 3 ) 3 ·1.5H 2 O phase during pretreatment with sufficient water vapor.…”
Section: Application To Dehydrated and Anhydrous Potassium Carbonatesmentioning
confidence: 99%